The Analysis Of Peer Roles On College Students’ Academic Performance - Jenifer Laura; Heri Pranoto, Yohanes (UKMC International Conference (UKMC IC) Proceedings, 2024)
It is widely acknowledged that peer relationships significantly influence students’ academic performance. The assumption that peer influence affects academic achievement encompasses various dimensions; including social, cognitive, and emotional aspects. Thus this concise qualitative case study aimed at the examination of the influence of peer relationships on the academic performance of college students particularly at Universitas Katolik Musi Charitas. Utilizing a questionnaire as the primary research instrument, 39 students from diverse study programs participated in the study. Those findings implied that educational institutions should prioritize fostering supportive and inclusive peer environments to enhance academic motivation and achievement among students even in the higher level of education.